The development of professional guidelines on the law and ethics of male circumcision. Issue 3 (1st June 2004) - Mussell, R
Abstract : This paper does not attempt to lay out the arguments relating to male circumcision for non-medical reasons. Rather, the aim is to focus more on the process and the problems of a professional body (in this case the British Medical Association (BMA)) attempting to produce any consensus guidelines for its members on an issue which clearly polarises doctors as much as it divides society as a whole. The legal and ethical considerations of male circumcision are inevitably touched upon here but are not the central issue. In 2003, the BMA published professional guidance on this subject. Some thought this a pointless exercise; others saw it as an initiative which simply failed to go far enough. Reservations centred on the fact that the BMA's guidance—like that of the statutory body, the General Medical Council—explored the issues without either firmly rejecting or accepting non-therapeutic male circumcision. Was it then a fruitless project or a brave start to grasping the nettle?